2017
DOI: 10.1111/1744-9987.12560
|View full text |Cite
|
Sign up to set email alerts
|

Protein Concentration of Refractory Ascites in Cancer Patients is Reflected by the Presence and Severity of Peritoneal and Liver Metastasis

Abstract: Ascites total protein concentration (A-TP) affects the performance of cell-free and concentrated ascites reinfusion therapy (CART). As the factors determining A-TP remain unclear, we examined peritoneal and liver metastasis. Among 98 patients who received CART, 68 with cancer, ascites from no other apparent cause, and complete CT and A-TP data were recruited. Sixty-six patients (97%) with peritoneal and/or liver metastasis on CT were divided into the peritoneal metastasis group (PM group), peritoneal and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Refractory ascites patients often develop hypoalbuminemia due reasons such as protein leakage into ascites 1 and body protein consumption by underlying diseases 2,3 . Since albumin is essential for the maintenance of colloid osmotic pressure, hypoalbuminemia can cause systemic swelling, intravascular dehydration, and prerenal failure 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory ascites patients often develop hypoalbuminemia due reasons such as protein leakage into ascites 1 and body protein consumption by underlying diseases 2,3 . Since albumin is essential for the maintenance of colloid osmotic pressure, hypoalbuminemia can cause systemic swelling, intravascular dehydration, and prerenal failure 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Ascites drainage by paracentesis is performed as a general non-drug treatment for refractory ascites 17,18 . During simple paracentesis, hypoalbuminemia may develop since large amounts of protein are drained and discarded 1 . To prevent hypoalbuminemia by the loss of ascites protein 19 , cell-free and concentrated ascites reinfusion therapy (CART) was developed in Japan in the 1970s 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we consider the increase in 2.0 g/dL of albumin to be sufficient, even though the differences were not significant in the present study. In another study, Yamada et al also demonstrated that total protein concentration in ascites could be determined by the presence with or without peritoneal or liver metastasis 11 . It is important to know these simultaneous comorbidities because we can assume the levels of total protein concentration ahead of paracentesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cell‐free and concentrated ascites reinfusion therapy (CART) has been widely used for malignant ascites in Japan [ 1 , 2 , 3 , 4 ]. This process is carried out by collecting the ascites from the patient followed by its filtration and concentration.…”
Section: Introductionmentioning
confidence: 99%